Contemporary theoretical reflections on built heritage and its significance - Villamón Guevara, Teresa (2018)
So that it may be formally recognized as such by national institutions and /or international bodies, built heritage is evaluated in a scale of historical, aesthetical and technological value. With such recognition as a starting point, the goal is to contribute to the formation of a cultural identity in a national or a regional scale through the management of the above-mentioned heritage. This identity would fit into the ideals of the insitutions or communities that legitimize such recognition. Nevertheless, in a local or domestic level, even though users of this heritage can recognize such values in an architectural object, these very users tend to attribute to that same object, in a scale of informal character, qualities that relate to a level of more intimate meaning. The following essay presents the contemporary academic discussion around the concept of heritage, and the different values it acquires among groups of formal actors –institutions and professionals from the field– and citizens. As well, it shows the tensions and dichotomies that the nature of built heritage itself produces among those who are related to it.